2011
DOI: 10.1021/ol2011117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Revision of Phomopsin B, a Novel Polyketide Carrying a 10-Membered Cyclic-Ether Ring

Abstract: Total synthesis of the proposed structure 2 for phomopsin B was achieved by using an intramolecular olefin metathesis as a key step. The spectral data, however, did not match with those of the natural product reported. Re-examination of the reported NMR data led to the structural revision of phomopsin B to known dothiorelone A 18. The R configuration of dothiorelone A was determined by total synthesis through a cross-metathesis with a chiral olefin 19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This study represents the first total synthesis of compounds 10c , 10d , 10f , 10g , 10h , and 10i . While we generally observed good agreement between our spectroscopic data and the data presented in the isolation reports, we found significant deviations in the 1 H and 13 C NMR data for compound 10f (see SI for a comparison table).…”
Section: Resultssupporting
confidence: 92%
“…This study represents the first total synthesis of compounds 10c , 10d , 10f , 10g , 10h , and 10i . While we generally observed good agreement between our spectroscopic data and the data presented in the isolation reports, we found significant deviations in the 1 H and 13 C NMR data for compound 10f (see SI for a comparison table).…”
Section: Resultssupporting
confidence: 92%
“…The authors suggested that the structure of phomopsin A was likely to require revision to that of dothioreline B 310 but as the 13 C NMR data of the two compounds were not identical, it might indicate that the 13 C NMR assignments for dothiorelone B also need reinvestigation. 311 Seragakinone A was originally isolated from an unidentied red alga-associated fungus. 312 The absolute conguration of the subsequently corrected structure 313 has been conrmed by synthesis of the enantiomer, (À)-seragakinone A.…”
Section: Synthetic Aspectsmentioning
confidence: 99%
“…However, sometimes, we could not obtain the structural fragments of a molecule and could only rely on the NMR and molecular formula for structural elucidation. To evaluate the performance of CMGNet with NMR and the molecular formula as conditions, we collected nine 13 C NMR spectra, whose originally determined structures were revised in later publications. In this task, we examined whether the model generated the correct molecules or preferentially generated the correct molecules by comparing the ranks of original structures and revised structures. Table shows four molecules that were not included in the training set.…”
Section: Resultsmentioning
confidence: 99%